German Registry for Cardiac Operations and Interventions in Congenital Heart Disease: Annual Report 2022 - Hofbeck, Michael; Arenz, Claudia; Bauer, Ulrike M. M.; Horke, Alexander; Kerst, Gunter; Meyer, Renate; Tengler, Anja; Beckmann, Andreas (The Thoracic and Cardiovascular Surgeon, 2024)
Background The German Registry for Cardiac Operations and Interventions in Patients with Congenital Heart Disease is a voluntary registry initiated by the German Society for Thoracic and Cardiovascular Surgery and the German Society for Pediatric Cardiology and Congenital Heart Defects. Since 2012, the registry collects data for the assessment of treatment and outcomes of surgical and interventional procedures in patients with congenital heart disease (CHD) of all age groups.Methods This real-world, prospective all-comers registry collects clinical and procedural characteristics, adverse events (AEs), mortality, and medium-term outcomes (up to 90 days) of patients undergoing surgical and interventional. A unique pseudonymous personal identifier (PID) allows longitudinal data acquisition in case of further invasive treatment in any participating German heart center. Prior to evaluation, all data sets are monitored for data completeness and integrity. Evaluation includes risk stratification of interventional and surgical procedures and classification of AEs. Each year's data are summarized in annual reports containing detailed information on the entire cohort, all subgroups, and 15 index procedures. In addition, each participating center receives an institutional benchmark report for comparison with the national results. This paper presents a comprehensive summary of the annual report 2021.Results In 2021, a total of 5,439 patients were included by 22 participating centers. In total, 3,721 surgical, 3,413 interventional, and 34 hybrid procedures were performed during 6,122 hospital stays. 2,220 cases (36.3%) could be allocated to the 15 index procedures. The mean unadjusted in-hospital mortality ranged from 0.4% among interventional and 2% among surgical cases up to 6.2 % in cases with multiple procedures. In-hospital mortality among index procedures accounted for 2.3% in total cavopulmonary connection, 20.3% in Norwood procedures, and 0.4% following interventional closure of patent ductus arteriosus. For the remaining seven surgical and five interventional index procedures, no in-hospital deaths were recorded. The 10-year longitudinal evaluation of 1,795 patients after tetralogy of Fallot repair revealed repeat interventional or surgical procedures in 21% of the patients. Over the same period, 31.1% of 2,037 patients, following initial treatment of native coarctation, required at least one additional hospital admission, 39.4% after initial interventional, and 21.3% after initial surgical therapy.Conclusion The annual report 2021 of the German Registry for Cardiac Operations and Interventions in CHD shows continuously good results in accordance with previous data of the registry. Compared to international registries on CHD, it can be ascertained that in Germany invasive treatment of CHD is offered on a high medical level with excellent quality. The proven fact that patients with various malformations like tetralogy of Fallot and coarctation of the aorta require repeat procedures during follow-up confirms the urgent requirement for longitudinal assessment of all patients presenting with complex lesions.
Keywords: congenital heart disease; outcomes; multicenter registry; pediatric cardiology; congenital heart surgery; transcatheter intervention; Fallot